Understanding radiation biology : from DNA damage to cancer and radiation risk - Chadwick, K. H. (Kenneth Helme), 1937- (Boca Raton : CRC Press, 2020)
"This book provides a qualitative and quantitative exploration of the action of radiation on living matter which leads to a complete and coherent interpretation of radiation biology. It takes readers from radiation-induced molecular damage in the nucleus of the cell and links this damage to cellular effects such as cell killing, chromosome aberrations and mutations and from there to organ damage, organism lethality and cancer induction. It also deals with radiological protection concepts and the difficulties of predicting the dose effect relationship for low dose and dose rate radiation risk. The book ends with separate chapters dealing with the effects of UV light exposure and risk classification of chemical mutagens, both of which are derived by logical extensions of the radiation model. This book will provide the basic foundations of radiation biology for undergraduate and graduate students in medical physics, biomedical engineering, radiological protection, medicine, radiology and radiography. Features: Presents a comprehensive insight into radiation action on living matter Discusses important implications for radiological protection and regulations Contains analytical methods for applications in radiotherapy Dr K H Chadwick, now retired, worked for twenty years at the Institute for the Application of Atomic Science in Agriculture at Wageningen in the Netherlands, employed by the European Commission. Dr Chadwick worked closely throughout his career with Dr H P Leenhouts, developing a theoretical model to describe the biological and health effects of radiation. In 1985, he moved to Brussels in Belgium to manage research contracts on radiation biological effects in the Euratom Radiation Protection Research Programme of the European Commission. He also served on the editorial board of the Journal for Radiological Protection for ten years and is a fellow of the Institute of Physics (FInst P) and the Society for Radiological Protection (FSRP)"--
OCLC-licensed vendor bibliographic record.
Keywords: Radiobiology; MEDICAL / Oncology